From shock to synchrotron: a mini-review on magnetic turbulence in supernova remnants - Greco, Emanuele (Frontiers in Astronomy and Space Sciences, 2025)
Magnetic turbulence plays a crucial role in confining charged particles near the shock front of Supernova Remnants, enabling them to reach energies up to hundreds of TeV through a process known as Diffusive Shock Acceleration (DSA). These high-energy electrons spiral along magnetic field lines, emitting X-ray synchrotron radiation. The launch of the Imaging X-ray Polarimetry Explorer (IXPE) has opened a new window into the study of magnetic fields in SNRs through X-ray polarization measurements. For the first time, IXPE allows us to resolve the polarization degree (PD) and angle (PA) in the X-ray band across different areas of SNRs, offering direct insight into the geometry and coherence of magnetic fields on different scales. In this mini-review, I summarize the key observational results on SNRs obtained with IXPE over the past 4 years and discuss their implications for our understanding of magnetic turbulence in synchrotron-emitting regions. I also show how we can combine polarization parameters and standard X-ray spectral/imaging analysis to better constrain the structure and scale of magnetic turbulence immediately downstream of the shock and understand the particle acceleration occurring in SNRs.